Optimized Design of the Lithium Niobate for Spectrally‐Pure‐State Generation at MIR Wavelengths Using Metaheuristic Algorithm. Issue 7 (21st April 2022) - Cai, Wu‐Hao; Tian, Ying; Wang, Shun; You, Chenglong; Zhou, Qiang; Jin, Rui‐Bo
Abstract: Quantum light sources in the mid‐infrared (MIR) band play an important role in many applications, such as quantum sensing, quantum imaging, and quantum communication. However, there is still a lack of high‐quality quantum light sources in the MIR band, such as the spectrally pure single‐photon source. In this work, the generation of a spectrally‐pure state in an optimized poled lithium niobate crystal using a metaheuristic algorithm is presented. In particular, the particle swarm optimization algorithm is adopted to optimize the duty cycle of the poling period of the lithium niobate crystal. With this approach, the spectral purity can be improved from 0.820 to 0.998 under the third group‐velocity‐matched condition, and the wavelength‐tunable range from 3.0 to 4.0 µm for the degenerate case and 3.0 to 3.7 µm for the nondegenerate case. This work paves the way for developing quantum photonic technologies at the MIR wavelength band. Abstract : The metaheuristic algorithm is introduced to the field of quantum state engineering to optimize lithium niobate. This method exploits the algorithm to design spectrally‐pure single photons for mid‐infrared wavelengths. The potential of this technique can be used to design special nonlinear crystals to generate exotic quantum states for quantum sensing and metrology in the mid‐infrared wavelengths for future applications.